2014
DOI: 10.1590/s1983-40632014000200012
|View full text |Cite
|
Sign up to set email alerts
|

Produção e qualidade de frutos de clones de videira 'Concord' sobre diferentes porta-enxertos

Abstract: Dentre as tradicionais cultivares utilizadas na elaboração de suco de uva, a 'Concord' tem se destacado pelo bom aroma e sabor que confere ao suco. Este trabalho objetivou avaliar a produção e qualidade dos frutos de seis clones de videira 'Concord'('22', '28', '49', '202', '211'e '225'), sobre três portaenxertos ('IAC 766', 'IAC 572' e '420-A'). O experimento foi realizado em Rolândia (PR), em esquema fatorial 6x3 (clones x porta-enxertos), em delineamento inteiramente casualizado, com cinco repetições e parc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
2
10
2
Order By: Relevance
“…Compared with 'IAC 572', 'IAC 766' provided lower pH and higher contents of soluble solids and titratable acidity for the grapes. In contrast to the results found in this study, 'IAC 766' and 'IAC 572' did not differ in affecting chemical attributes (pH, SS, TA and SS/ TA) of Concord grapes (Borges et al, 2014). Thus, the performance of rootstocks is not always uniform, and rootstocks must be tested for each cultivar and location.…”
Section: Physicochemical Characteristics Of the Grapescontrasting
confidence: 95%
See 1 more Smart Citation
“…Compared with 'IAC 572', 'IAC 766' provided lower pH and higher contents of soluble solids and titratable acidity for the grapes. In contrast to the results found in this study, 'IAC 766' and 'IAC 572' did not differ in affecting chemical attributes (pH, SS, TA and SS/ TA) of Concord grapes (Borges et al, 2014). Thus, the performance of rootstocks is not always uniform, and rootstocks must be tested for each cultivar and location.…”
Section: Physicochemical Characteristics Of the Grapescontrasting
confidence: 95%
“…'IAC 766' favored increases in mass, length, and width of bunches and berries, compared with those in 'IAC 572' (Table 2). Borges et al (2014) did not observe significant differences between 'IAC 766' and 'IAC 572' for number of bunches per vine and bunch mass for the 'Concord' variety, which indicates that different varieties respond differently to the use of the same rootstocks. In varieties of V. vinifera table grapes, the number of berries per bunch, berry diameter, berry mass and rachis mass showed great variability using the same rootstocks (Ibacache et al, 2016).The level of vigor conferred by different rootstocks to scions may be a fundamental factor in changing the physical attributes of grapes (Bascunán-Godoy et al, 2017).…”
Section: Physicochemical Characteristics Of the Grapesmentioning
confidence: 72%
“…For Isabel Precoce, Isabel and Concord cultivars, intermediate bunch fresh weight values were obtained, ranging from 126 to 148.4g. Bunch fresh weight were similar to those reported in literature for Isabel cultivar (SANTOS et al, 2011;SATO et al, 2009;RIZZON and MIELE, 2006) and higher than those found for Concord cultivar (ANZANELLO et al, 2008;BORGES et al, 2014).…”
Section: Resultssupporting
confidence: 89%
“…BRS Violeta cultivar showed high productivity in the CD system because it compensates the low number of bunches produced by vines by the greater bunch fresh weight. Yield values for 'Concord' observed in this study were higher than those reported by Borges et al (2014) for vines trained in pergola (10.9 t ha -1 ) in Rolândia -PR.…”
Section: Number Of Bunches-contrasting
confidence: 82%
See 1 more Smart Citation